Aktualne tendencje orzecznicze w sprawach finansowych ochotniczych straży pożarnych - Kała, Dariusz P. (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The aim of the study is to present the latest and current judicial trends in financial issues regarding volunteer fire. You should not pay a cash equivalent for participating in emergency and rescue exercises.Based on Article. 32 para. 3b of the Fire Protection Act, subsidies for volunteer fire brigades may be planned in the commune budget. Compensation and compensation for members of volunteer fire brigades is exempt from tax.
Keywords: volunteer fire brigade; equivalent; compensation; subsidies; financing of voluntary fire brigades